Integrated Metabolomics and Network Pharmacology Revealed Hong-Hua-Xiao-Yao Tablet’s Effect of Mediating Hormone Synthesis in the Treatment of Mammary Gland Hyperplasia - Gao, Ziqing; Mi, Rui; Cheng, Zhaoxi; Li, Xiaofeng; Zeng, Huawu; Wu, Gaosong; Zhao, Jing; Zhang, Weidong; Ye, Ji (Frontiers in Pharmacology, 2022)
Hong-Hua-Xiao-Yao Tablet (HHXYT) is a traditional Chinese medicine (TCM) formula that has been approved for the treatment of mammary gland hyperplasia (MGH), but its mechanism of action is unclear. In this study, a strategy that integrated metabolomics and network pharmacology was applied to systemically reveal the mechanism of HHXYT in the treatment of MGH. Our pharmacodynamic study indicated that the proliferation of mammary gland was inhibited in rats, and serum-level disorder of estradiol and progesterone was reversed after HHXYT treatment. 54 compounds absorbed in rat plasma were identified after administration of HHXYT. The serum metabolome revealed 58 endogenous differential metabolites, of which 31% were steroid lipids metabolites, with steroid hormone biosynthesis being the most significant metabolic module. 7 targets, 6 herbs, and 17 ingredients were found to play key roles in HHXYT’s treatment of MGH. 3 of the 7 key targets (CYP11A1, HSD3B2, and CYP17A1) were directly involved in androgen synthesis, while 2 targets (AR and ESR1) were receptors for the direct action of androgens and estrogens. Molecular docking was utilized to confirm the bindings between the 5 targets and their corresponding compounds. In an in vitro test, HHXYT (50 µg/ml) and its ingredient formononetin (3.2, 6.3, and 12.5 µM) were found to significantly reduce the increase of testosterone level induced by dexamethasone (10 µM) in thecal cells. In summary, this study illustrated that the mechanism of HHXYT’s treatment of MGH was to regulate hormone disorder. HHXYT could reduce estrogen-stimulated hyperplasia by inhibiting the production of its precursor androgen.